32.1k views
19 votes
Select all the statements that are true. Explain your reasoning

4−2(3+7)=4−2⋅3−2⋅7
4−2(3+7)=4+−2⋅3+−2⋅7
4−2(3+7)=4−2⋅3+2⋅7
4−2(3+7)=4−(2⋅3+2⋅7)

User OneStig
by
5.5k points

1 Answer

4 votes

Answer:

First and second are both true.

Third and fourth are not true.

Explanation:

4−2(3+7)=4−2⋅3−2⋅7

4−2(3+7)= 4 - 2(3+7) [ -2*3 - 2*7 : the -2 can be removed from -2*3-2*7 to make -2(3 + 7); communative] This results in 4-2(3+7), the same on the left side

4−2(3+7)=4+−2⋅3+−2⋅7

The (4+-2*3+-2*7) can be written as (4-2*3-2*7) to simplify the "-+" to simply "-". That can be written as 4 - 2(3+7), the same as on the left side.

4−2(3+7)=4−2⋅3+2⋅7

The right side, 4-2*3+2*7, can be written as 4-2(3-7), which is NOT the same as on the left.

4−2(3+7)=4−(2⋅3+2⋅7)

The right side can be written as 4-2(3-7), which is not the same as on the left side.

User Cherri
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.